Aluminium Nitride Thin Film Deposition Using Magnetron Sputtering on Silicon and Microscopic Glass Substrate for IDE Applications - Samynathan, Mugilesh; Mohamed Ali, Riyaz Ahmad (Evolution in Electrical and Electronic Engineering, 2024)
This work aims to investigate the potential of magnetron sputtering to deposit thin aluminium nitride films on microscopic glass and silicon substrates. The objective is to examine the advantages and limitations of magnetron sputtering and its potential challenges for healthcare applications and other fields. Magnetron sputtering is a promising technique that produces high-quality, uniform films with good adhesion and low defect density. The findings suggest that magnetron sputtering has significant potential to improving the sensitivity of medical diagnostic tools, enhancing drug delivery systems, and enabling the development of advanced biosensors. The study also investigates the impact of magnetron sputtering on the thickness, roughness, and electric conductivity of aluminium nitride (AlN) thin film deposited on silicon and microscopic glass substrates. The results show that increasing the duration of sputtering leads to thicker and smoother aluminium nitride film deposition. Additionally, the use of silicon and microscopic glass as substrates to deposit thin aluminium nitride film for IDE (interdigitated electrode) applications helps to study which substrate can eliminate the influence of the substrate on the electric conductivity reading of the thin aluminium nitride film.